Associations among inflammation, mental health, and quality of life in adults with metabolic syndrome - Ji-Ryang Kim; Ha-Na Kim; Sang-Wook Song (Diabetology & Metabolic Syndrome, 2018)
Abstract Background Metabolic syndrome (MetS), a pro-inflammatory state, has become increasingly common worldwide and is a major risk factor for type 2 diabetes mellitus and cardiovascular disease. Recently, studies on the relationships among inflammation, mental health, quality of life, and other diseases have been conducted. Methods We investigated the relationship between serum high-sensitivity C-reactive protein (hs-CRP) levels, as an indicator of inflammation, and the quality of life and psychiatric symptoms of Korean adults with MetS. The analysis used data from the Korean National Health and Nutrition Examination Survey, a cross-sectional survey of Korean civilians conducted from January to December 2015. Data from 1600 participants were analyzed in this study. Quality of life was assessed using the EuroQol 5-dimension (EQ-5D) instrument. Results Serum hs-CRP levels showed a significant inverse correlation with the EQ-5D index of the overall quality of life. High serum hs-CRP levels were positively associated with mobility problems and suicidal ideation in adults with MetS (multivariate-adjusted odds ratio [OR] 1.66, 95% confidence interval [CI] 1.03–2.66, p = 0.036; and multivariate-adjusted OR 2.48, 95% CI 1.23–4.99, p = 0.011). Conclusions These findings suggest that the elevated inflammatory status in MetS is associated with decreased quality of life and mental health problems. Further prospective studies are needed to confirm the impact of inflammation on the quality of life and mental health of adults with MetS.